CORRELATION BETWEEN THE LENGTH OF THE DENTAL ROWS AND THE TOPOGRAPHOANATOMIC INDICATORS OF THE ARTICULAR DISK (MENISCUS) IN THE PATIENTS WITH DYSFUNCTIONAL CONDITIONS ACCORDING TO MRI DATA - Y.S. Lunkova; O.B. Tumakova; V.M. Novikov (Ukrainian Medical Stomatological Academy, 2017)
Objective is to investigate the interconnections of the mesiodistal dimensions of occlusal surfaces of teeth and structural elements of the temporomandibular joint with its internal disorders. The results of the MRI, measurements of the length of the tooth row and the mesiodistal size of the crowns of the upper and lower jaws according to our modified Nance method, the Tay-b Kendell criterion was used to analyze the interconnections within the groups. A statistically significant (p˂0,05) relationship between the sums of mesiodistal sizes of crowns of the teeth of the upper and lower jaws, the length of the tooth row (measured in the mesiodistal plane on the occlusal surface of the teeth) of the upper and lower jaws, as well as with anatomical and topographical changes of the articular disks on the right and left sides with closed and opened mouth were found. Thus, there is an effect not only of the vertical but also of the horizontal characteristics of the structural elements of the TMJ on the topographic-anatomical interrelation of the elements of the TMJ.